Екологічні аспекти розвитку міжнародного транспортного коридору Європа–Азія - Чернявський, Ю.І. (Економіка природокористування і охорони довкілля, 2013)
Розглянуто вплив функціонування міжнародного транспортного коридору Європа – Азія на екологічну ситуацію в Україні та запропоновано заходи, що дозволяють знизити вплив транспорту на довкілля. Influence of functioning of the international transport corridor Europe - Asia on ecology of Ukraine and measures which allow to reduce influence of transport on an environment is considered in this articl. It is possible to make users bear certain environmental costs resulting from their use of transport, particularly where they use transport infrastructures («polluter pays» principle). This taking account of external environmental costs in infrastructure charging is authorised by two sectoral Directives. There is, however, no common legislative framework for all transport modes that would propose a common methodology and timetable in order to avoid distortions of competition. The growth in vehicle numbers and use is a threat to the environment and the health of Ukraine citizens.